Effectiveness of interviewing techniques with the black child during forensic social work assessments : South African perspective - Rapholo, Selelo Frank (My University, 2018)
Child sexual abuse is a serious social and health issue that affects people worldwide. A variety of professions is trying to address this problem. It has numerous consequences, such as psychological, physical, social and emotional effects. An integral part of fighting child sexual abuse is disclosure. Forensic social work has been introduced in South Africa recently to facilitate the disclosure of child sexual abuse. This study aimed at evaluating the effectiveness of interviewing techniques with the Black child during forensic social work assessments in a South African perspective. The ecosystems theory was used in this research study to zoom into the nature of child sexual abuse and the environmental systems in South Africa that may affect the effectiveness of the interviewing techniques during forensic assessments with Black children. The study employed qualitative and evaluation designs. Non-probability sampling and probability sampling methods aided triangulation. Stratified random sampling, purposive sampling and convenient sampling techniques were followed to select fourteen (14) forensic social workers in South Africa. Out of these forensic social workers, thirteen (13) were females and one (1) was a male. Data were collected by means of a literature review and semi-structured in-depth interviews guided by an interview schedule with open-ended questions. The collected data were analysed thematically with the help of the Nvivo programme. The study revealed that rape is the most common sexual offence against Black children that forensic social workers across South Africa address. For the purpose of this research, rape is defined in accordance with the Criminal Law (Sexual Offences and Related Matters) Amendment Act 32 of 2007. Other sexual offences such as sexual assault, sexual grooming, and sexual exploitation/labour are barely reported because some South African communities regard them as minor things or taboos that could be addressed within families. As a result, they are not given the same recognition as rape in South Africa. Forensic social workers therefore have fewer such cases. The study also revealed that child pornography or exposing children to explicit sexual materials takes place more in urban areas than in rural areas, and as a result, it is not assessed among Black children in rural areas. This study further reveals that the disclosure of child sexual abuse is a process where children only disclose to someone whom they trust. In this regard, the environment where children are raised contributes to the disclosure of child sexual abuse. In rural areas, child xiv sexual abuse is mostly disclosed accidentally. Children from urban areas disclose more deliberately. Findings point to factors such as fear of the perpetrator, relationship with the perpetrator, boundaries of culture, the environmental setting, fear of embarrassment and shame, age of the child, language competency, poverty and the South African justice system as factors that play a role in disclosure of child sexual abuse during forensic social work assessments. In the facilitation of the disclosure of child sexual abuse, there is a variety of dynamics that professionals should be watchful of that may influence the disclosure rate. Personal characteristics of the child and the interviewer may affect disclosure of child sexual abuse during forensic interviews. For forensic social workers to ensure the protection of children and the conviction of perpetrators in child sexual abuse cases, they have to conduct skilful forensic interviews. There are specific interviewing techniques that aid disclosure. Some of these techniques appear to be very effective at eliciting detailed and accurate disclosures. Research reveals that in South Africa, cultural background, developmental level, language barriers and the manner of questioning children have an impact in the effectiveness of interviewing techniques during the assessments of allegations of child sexual abuse. Techniques should be contextualized in terms of cultural backgrounds and one should consider developmental level (age in particular), types of questions and language of the child, especially for Blacks. Once again, the disclosure of sexual abuse is a process with definable phases and characteristics. Many children find it difficult to talk about their sexual abuse experiences. It is therefore imperative that forensic social workers have an understanding of the diagonal process of disclosure when conducting forensic assessments. Forensic social workers have to be watchful of varied dynamics that are likely to affect the disclosure rate. The findings reveal that personal characteristics of the child and the interviewer, communication skills, blind assessments and informed allegation interviews have an impact on making the interviewing techniques effective during the disclosure of child sexual abuse. As a result, the study recommends that the forensic social worker should come to the developmental level of the child, speak the language of the child or use interpreters for the child to understand, and follow blind assessments interviews as opposed to informed allegation interviews. However, informed allegations interviews are recommended when assessing children below the age of four (4) years.
Thesis (Ph. D. (Social Work)) --University of Limpopo, 2018
Keywords: Child sexual abuse; Interviewing techniques; Forensic social work assessment; Interviewing; Interviewing - Technique; Social work